The many-minded man: the Odyssey, psychology, and the therapy of epic - Christensen, Joel (Myth and poetics II, 2020)
"Argues that the Odyssey explores the development and dysfunction of human minds and provides for its audiences-both ancient and modern-a basic theory of human mental function and identity as well as approaches or treatments when the mind in some way fails"--